General Decay for the Degenerate Equation with a Memory Condition at the Boundary. (27th March 2013) - Shin, Su-Young; Kang, Jum-Ran
Abstract : We consider a degenerate equation with a memory condition at the boundary. For a wider class of relaxation functions, we establish a more general decay result, from which the usual exponential and polynomial decay rates are only special cases.